NiSe Nanowire Film Supported on Nickel Foam: An Efficient and Stable 3D Bifunctional Electrode for Full Water Splitting1. Issue 32 (1st July 2015) - Tang, Chun; Cheng, Ningyan; Pu, Zonghua; Xing, Wei; Sun, Xuping
Abstract Active and stable electrocatalysts made from earth‐abundant elements are key to water splitting for hydrogen production through electrolysis. The growth of NiSe nanowire film on nickel foam (NiSe/NF) in situ by hydrothermal treatment of NF using NaHSe as Se source is presented. When used as a 3D oxygen evolution electrode, the NiSe/NF exhibits high activity with an overpotential of 270 mV required to achieve 20 mA cm−2 and strong durability in 1.0 M KOH, and the NiOOH species formed at the NiSe surface serves as the actual catalytic site. The system is also highly efficient for catalyzing the hydrogen evolution reaction in basic media. This bifunctional electrode enables a high‐performance alkaline water electrolyzer with 10 mA cm−2 at a cell voltage of 1.63 V.